Islamist-Secular Cleavages at Tunisia ́s Universities - Tho Seeth, Amanda (International Higher Education, 2016)
This article shows how the struggle between secularist and Islamist forces has entered Tunisia´s universities since the introduction of democracy in 2011. In the new political freedom, Islamist voices have become more powerful at the campuses. The Islamist student organization UGTE for the first time ever won the elections over the student councils in November 2015. A future constant rise and stabilization of Islamist power over academia could be backed up by the current weakness of the secular parties in parliament. Furthermore, since democratization, universities have become targets of Salafist violent protests and are affected by the temporary curfews imposed after recurrent terrorist attacks by The Islamic State (IS) in the country.